An Analysis of students’ anxiety factors of EFL students’ speech production - Zahratul Fikni (Jurnal Langua, 2022)
English Foreign Language (EFL) students are considered to have mastered English when they can speak English fluently, as evidenced by their speech production. Nevertheless, becoming fluent and competent is particularly difficult for foreign language learners because it is influenced by several factors. Among the several factors that affect foreign language learning, especially speaking, anxiety emerges as the crucial one that has a debilitating effect on the oral performances of students. This study was proposed to analyze the speaking anxiety level and factors of English Foreign Language students’ anxiety in speech production. The data were gathered from qualitative research with random sampling conducted in the second semester, consisting of 30 students taking the Speaking for Academic Communication class at Hamzanwadi University. A closed-ended questionnaire of the Foreign Language Classroom Anxiety Scale and semi-structured interviews were administered to the participants to explore the anxiety level and the factors of their anxiety in speech production. The results indicate a high level of anxiety among students when speaking English. Key factors contributing to their speaking anxiety include audience shyness, fear of miscommunication, lack of preparation, low self-confidence, and low proficiency.